ISOLASI DAN UJI SITOTOKSIK SENYAWA LIMONEN DARI KULIT BATANG KASTURI (Mangifera casturi) - Kholifatu Rosyidah (Bioscientiae, 2011)
The air-stem barks of M.casturi were extracted with Methylene Chloride (MTC). The MTC extract’s had treatment with Brine Shrimp Lethality Test (BSLT) than analyzed with probit and resulted LC50= 47,31 ppm. MTC extract’s was fractionated by Vacuum Liquid Chromatography and recrystalization obtained pure compounds. The compounds was analyzed with GC-MS (Gas chromatography-Mass Spectroscopy) and cytotoxic test with cancer cell Leukemia P388. This compound is limonene and have IC50=70 ppm.